The reality on the ground – placing Indonesian halal cosmetics onto the international pedestal - Helma Malini; Benedict Valentine Arulanandam; Rizqi Maghribi (Faculty of Business & Economics, Universitas Islam Indonesia, 2021)
Purpose: The global halal industry has been making ground over the past decade in every sector of the worldwide economy. Indonesia is not left out in progress, considering its vast potential to develop the halal industry. This empirical study narrows down to the influence of halal labeling in the cosmetic industry as an export driver towards the economy of Indonesia.Methodology: This study undertakes a mixed-method approach drawing on quantitative and qualitative data. An in-depth face-to-face interview (with social distancing) was held using an interview guide, coupled with a survey questionnaire targeting regulators and manufacturers.Findings: The findings proved that halal certification, cosmetic quality, and brand image simultaneously affect buying decisions of cosmetics. Meanwhile, the Majelis Ulama Indonesia (MUI) recommends that cosmetics from Indonesia have a great opportunity to export. However, based on the results of interviews with cosmetic companies, they do not understand the concept of Maqashid al Syariah financing, which can integrate with the concept of halal products. Lastly, the cost of halal certification sometimes still burdens small-scale cosmetic companies, so support from the government is needed to encourage them to join the halal certification program.Originality: The research findings are helpful for the industry and regulators to address the export capabilities of Indonesian cosmetics. It provides an insight into the challenges and practical hindrances within the industry.